PH: the silent variable significantly impacting meiotic spindle assembly in mouse oocytes. Issue 3 (September 2018) - Swearman, Harriet; Koustas, George; Knight, Emily; Liperis, Georgios; Grupen, Christopher; Sjoblom, Cecilia
Abstract: Research question: Temperature fluctuation negatively impacts the assembly and function of the meiotic spindle, but does pH have a similar effect? Design: Polarized light microscopy was used to study the spindle in living mouse oocytes under different pH conditions. Female mice ( n = 53) were superovulated, and oocytes collected, denuded and allocated to treatment groups. All experiments were performed at 37°C, and standard bicarbonate-buffered medium was used either pre-equilibrated in 6% CO2 or unequilibrated (in ambient CO2 ). Mean oocyte spindle retardance was measured over time in response to changing pH. Spindles were also assessed to understand whether this effect was reversible, by using a fixed pH in a zwitterionic buffer. Results: The data show the spindle is impacted by pH fluctuation, with mean retardance significantly higher at pH 7.4–7.5 than at the point of media equilibration ( P  < 0.001). This effect was found to be reversible; retardance significantly decreased after transition of the oocytes from pH 7.43 or pH 7.53 back to the original pre-equilibration pH of 7.32 ( P  < 0.05). Conclusions: This study has shown that the meiotic spindle in mouse oocytes is highly sensitive to changes in oocyte culture media pH. If comparable in humans, this has significance as to the pH level of culture media currently used in assisted reproductive technology clinics worldwide, and reinforces the requirement for stringent control over extrinsic variables in the IVF laboratory.